Reviving Waqf through crowdfunding platform: an opportunity for Thailand - Mohd. Zain, Nor Razinah; Mohd Noor, Azman (2019)
Disruption of technology continues to change the global market and economy today. Simultaneously, Islamic social finance and its mechanisms are continued to gain spotlights due to their viability and sustainability nature. They are not only offering chances to achieve Sustainable Development Goals (SDGs) but also beyond such goals. Looking into application of Waqf as one of Islamic social finance’s instruments, this continuous charitable giving is preferred due its features that are perpetual, irrevocable, and inalienable. In Thailand, reviving and sustaining Waqf properties are still limited due to the lack of funds. However, with the existence of new technology called crowdfunding platform, the revival of Waqf can be made possible. Such revival of Waqf is essential for the society at large, especially for the Muslim community. The revival of Waqf may provide essential assistance in alleviating poverty and gives an equal opportunity for an economic participation. By using a qualitative research method and documentary-based legal analysis, this research looks at the opportunity of reviving Waqf in Thailand through crowdfunding platforms.